Поляризовність двошарового метал-оксидного нано-дроту - Korotun, A.V.; Karandas, Ya.V.; Reva, V.I.; Titov, I.M. (Publishing house "Academperiodika", 2021)
Frequency dependences have been obtained for the real and imaginary parts and the absolute values of the components of the polarizability tensor of metal-oxide nanowires, as well as for the absorption and scattering cross-sections. The limiting cases of the ‘thick ” and “thin ” outer oxide layers are studied. Numerical calculations are performed for Al, Cu, and Ag wires coated with a corresponding oxide layer. The models where the dielectric constant of an oxide is either a constant or a function of the frequency are considered. In the last case, experimental frequency dependences of the refractive and extinction indices are used. The influence of the oxide layer thickness on the frequency dependences of the polarizability and the absorption and scattering cross-sections is analyzed. It is found that the presence of an oxide leads to a decrease in the frequency of surface plasmons in two-layer nanowires due to the influence of classical size effects.